Stability study of oral strip for anti-allergic film olopatadine hydrochloride (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The aim of the present work was to develop and evaluate the fast-dissolving oral films (FDF) ofolopatadine hydrochloride which is used for the treatment of anti-allergic. This study was to perform evaluationstudy of film stability, their stability of oral strip in different temperature for the easy to transport in different areasthat they are not damage for the temperature conditions. Materials and Methods: The olopatadine hydrochloridefilm was prepared by solvent-casting method which is used for prepared oral strip such as hydroxypropylmethylcellulose (HPMC), maltodextrin, and polyethylene glycol, as plasticizers different polymers are used.Results: The prepared oral strip showed satisfactory results for the evaluation parameters oral strip as optimizedbatch was evaluated for stability of film in different temperatures that are used as an in vitro test for the evaluationof film for storage in different temperatures and their transportation stability. Olopatadine hydrochloride FDF wasdeveloped and evaluated for weight uniformity in vitro dispersion time, in vitro dissolution time, drug content,and film thickness that the results obtained were within the specified limits. Temperature stability test is usedfor high temperature evaluated in hot air oven, and low temperature evaluated in refrigerator. Conclusion: TheFDF prepared with HPMC E-15, at 2, 4, 6, and 8 ratio released the drug up to 98.7% within 2 s which evaluatedthat their stability study in different temperatures which are evaluated showed that their stability studies wereconducted for pure drug, polymers, and optimized formulation f6 which indicated that found between the drugand polymers used in the present studies evaluated that the film is stable in different temperature, polymers, andoptimized formulation F6 which showed that they were no surface fractures and cracks in the films.